Associations between smoking status and infertility: a cross-sectional analysis among USA women aged 18-45 years - He, Sijie; Wan, Li (Frontiers in Endocrinology, 2023)
Background Although many studies have proven the harmful effects of smoking on human health, the associations between smoking status and infertility are limited in large epidemiologic studies. We aimed to investigate the associations between smoking status and infertility among child-bearing women in the United States of America (USA). Methods A total of 3,665 female participants (aged 18-45) from the National Health and Nutrition Examination Survey (NHANES) (2013-2018) were included in this analysis. All data were survey-weighted, and corresponding logistic regression models were performed to investigate the associations between smoking status and infertility. Results In a fully adjusted model, the risk of infertility was found to be increased by 41.8% among current smokers compared to never smokers (95% CI: 1.044-1.926, P=0.025). In the subgroup analysis, the odds ratios (95% CI) of the risk of infertility for current smokers were 2.352 (1.018-5.435) in the unadjusted model for Mexican American, 3.675 (1.531-8.820) in the unadjusted model but 2.162 (0.946-4.942) in fully adjusted model for people aged 25-31, 2.201 (1.097-4.418) in the unadjusted model but 0.837 (0.435-1.612) in fully adjusted model for people aged 32-38. Conclusion Current smokers was associated with a higher risk of infertility. The underlying mechanism of these correlations still needs more research. Our findings indicated that quitting smoking may serve as a simple index to reduce the risk of infertility.